How do farmers respond to rural development policy challenges? Evidence from Macedonia, Serbia and Bosnia and Herzegovina - Martinovska Stojcheska, Aleksandra; Kotevska, Ana; Bogdanov, Natalija; Nikolić, Aleksandra (Elsevier BV, 2016)
Rural development policy reforms and necessary institutional adjustments are of particular importancein overcoming the transitional challenges for the Western Balkan countries, whose economies are highlydependent on agriculture. The complex rural development context in these countries triggers the needfor better understanding and explaining of the factors influencing the use of rural development pol-icy funds. The research aim is to identify how the behavioural determinants and some socio-economiccharacteristics influence farmers’ intention to apply for rural development support (RDS). The analyti-cal framework is based on the theory of planned behaviour and structural equation modelling by usingfarm survey data collected in Macedonia, Serbia and Bosnia and Herzegovina in 2014. The results suggestthat the success of RDS depends on farmers’ underlying psychological constructs. The intention to useRDS funds is stronger with farmers with positive attitudes (in all three countries), support from the socialenvironment (in Serbia and Bosnia and Herzegovina) and higher perceived behavioural control (in Bosniaand Herzegovina and Macedonia). Prior experience with applying for RDS funds has positive effects onforming farmers’ intention to apply for RDS, while the influence of age, education and perceived farmprofitability on the behavioural determinants is less pronounced. Investigating the farmer’s behaviour inthese Western Balkan countries provides novel insights that could be used for related policy strategies.
Keywords: Rural development policy support; Western Balkans; Theory of planned behaviour; Structural equation model